Analysis of heavy metal content in emissions from shell, fiber, and empty fruit bunch biomass fuels (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Riau Province is one of the largest palm oil producers in Indonesia, where palm oil mills use boilers as a primary component to generate steam energy for processing activities. At PT TH Indo Plantation, particularly at Pulai Palm Oil Mill, biomass fuels such as palm kernel shells, fibers, and empty fruit bunches are commonly used. Boiler operations are often associated with emissions that may pose environmental and health risks. This study aims to analyze the heavy metal content in emissions from these biomass fuels. The research employed quantitative methods, including proximate and ultimate analyses, as well as spatial modeling using AERMOD to observe emission dispersion. The results showed relatively low heavy metal content: 0.01% in palm kernel shells and empty fruit bunches, and 0.02% in fibers. AERMOD simulation indicated that the concentration of PM2.5-type particulate matter reached 3.31311 µg/m³, with dispersion extending up to 3 km from the source. Based on these findings, the use of shell, fiber, and empty fruit bunch fuels at Pulai Palm Oil Mill does not result in significant environmental impact related to heavy metal dispersion and may be considered relatively safe.
Keywords: Boiler; heavy metal content; AERMOD